Efeito agudo do exercício step intervalado nos parâmetros cardiovasculares de mulheres hipertensas na pós-menopausa: estudo clínico, controlado e randomizado - Rodrigues, Mateus de Lima (2021)
Introduction: Systemic arterial hypertension (SAH) is a multifactorial clinical condition, more prevalent in women after menopause than in men of the same age. Aiming at the prevention and treatment of this disease, the standard positions indicate the performance of aerobic activity of moderate intensity that lasts more than 30 minutes per session. However, some studies have shown that interval exercise is capable of promoting post-exercise hypotension (PEH) of greater magnitude than continuous exercise. Objectives: To compare the effect of interval step exercise with continuous walking exercise on the cardiovascular parameters of post-menopausal hypertensive women. Material and methods: The volunteers were submitted to three experimental sessions: control (CO), interval exercise (EI) and continuous exercise (EC), in randomized order. The sessions lasted 120 minutes and during this period, resting blood pressure (PArep) was evaluated in 10, 90, 105 and 120 minutes, heart rate variability (HRV) in minutes 0 and 90 and blood pressure reactivity (RPA) to the Stroop Color-Word test in minutes 10 and 120. Evaluations in minutes 0 and 10 were performed pre-exercise and evaluations in minutes 90, 105 and 120 were performed post-exercise. Results: The study ended 12 women, postmenopausal, hypertensive medicated with an average age of 59 ± 4 years and an average BMI of 29.78 ± 4.10 kg / m². There was a reduction in systolic and mean BPrep (p = 0.008; p = 0.038), an increase in heart rate (HR) (p <0.001), a reduction in SDNN (p = 0.017) and RMSSD (p = 0.037) indices of HRV and a reduction in HRV of systolic RPA (p = 0.031) in exercise sessions, when compared to control, but with no difference between exercise sessions. Conclusion: Interval step exercise reduces blood pressure after exercise, but does not attenuate blood pressure reactivity and does not promote a PEH superior to continuous walking exercise.